Complications Of Suppurative Otitis Media Still Occur In The 21st Century - Mostafa Othman; Hamza alshafae; Emaad alfasse (Sirte Journal of Medical Sciences, 2022)
Chronic suppurative otitis media is chronic inflammation affected the middle ear and divided in 2 types benign and malignant type, Where the complication most aggressive with the malignant type. This study is aretrospective chart review for files of patients with suppurative otitis media complicated with one or more of the cranial and or intra-cranial complications of CSOM and attended to Assiut University Hospital (AUH) for management of their diseases during the 10 years from 1- 1-2005 to 31-12-2014. The patients were grouped into 3 groups: Group I: - with Cranial complications. Group II: - with Intra-cranial complications. Group III: - with mixed complications. The aim of study was to Identification of cases with different cranial and intra-cranial complications of suppurative otitis media that presented to AUH from 1-1-2005 to 31-12-2014, analyzing the factors surrounding these patients with complications, and Identification of the ways of management done.